International Relations of German Neurosurgeons after 1945 and the Evolution of the European Association of Neurosurgical Societies - Collmann, Hartmut; Eisenberg, Ulrike; Steudel, Wolf-Ingo; Piek, Jürgen (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2025)
International relationships of early German neurosurgeons had a long tradition. These connections had been cut off after World War II and could initially be re-established only at a personal level. In this context, Klaus Joachim Zülch, Kurt Schürmann, Hans Werner Pia, Friedrich Loew, and Arist Stender played a significant role. It took nearly two decades to establish good connections at an institutional level. During this process, major support came from France and should be considered as part of a growing cooperation of European states in various fields. The 1959 meeting of French, Swiss, and German neurosurgeons in Zürich was a crucial event, which ultimately led to the foundation of the European Association of Neurosurgical Societies.
Keywords: Acta Neurochirurgica; Marcel David; Hugo Krayenbühl; EANS; German Democratic Republic